(3JgPjH GdCNdGbs - (3GHf YOj , jMji Hf YOj Hf MejO Hf RcQjG, CHh RcQjG,J (B364 (3g` s
(3ChdgG (B:s
(3bGd CYde Cf GdEfSGf ef Hjf SGFQ GdMjhGf Ph acQ hJejjR s
(3BNQgG (B:s
(3aeG CbHM GdfbU HGdbGOQ Ydi GdJeGe hGdYLR ef GdceGd hgPG Mjf fNJe Gdbhd ai JgPjH GdCNdGb s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B156 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B211s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeLGejYs